2020
DOI: 10.1177/1040638719896327
|View full text |Cite
|
Sign up to set email alerts
|

Transmissible spongiform encephalopathy in goats: is PrP rapid test sensitivity affected by genotype?

Abstract: Transmissible spongiform encephalopathy (TSE) surveillance in goats relies on tests initially approved for cattle, subsequently assessed for sheep, and approval extrapolated for use in “small ruminants.” The current EU-approved immunodetection tests employ antibodies against various epitopes of the prion protein PrPSc, which is encoded by the host PRNP gene. The caprine PRNP gene is polymorphic, mostly at codons different from the ovine PRNP. The EU goat population is much more heterogeneous than the sheep pop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 28 publications
(46 reference statements)
0
4
0
Order By: Relevance
“…A recent study in goats demonstrated that rapid screening tests performed well in clinically affected animals but were less sensitive in the pre-clinical phase, which was dependent on PRNP polymorphisms. In particular, the presence of the M 142 allele appeared to compromise to some extent the sensitivity of the Bio-Rad screening tests (Simmons et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study in goats demonstrated that rapid screening tests performed well in clinically affected animals but were less sensitive in the pre-clinical phase, which was dependent on PRNP polymorphisms. In particular, the presence of the M 142 allele appeared to compromise to some extent the sensitivity of the Bio-Rad screening tests (Simmons et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…To assess whether false negative results in the screening ELISA test were associated with higher optical density (OD) values than true negative results, OD values for each sample were divided by the cut-off specified for each test run to calculate an OD cut-off ratio (multiplied by 100). The ratios were grouped by PRNP genotype at codon 142 based on recent findings that PRNP polymorphisms may affect test sensitivity in goats (Simmons et al, 2020), and the data compared by non-parametric Mann-Whitney U-test. This test was also used to compare the ages of goats with a false negative and true negative ELISA result, grouped by genotype at codon 142.…”
Section: Statistical Calculationsmentioning
confidence: 99%
“…A further confounding issue when considering diagnostic screening test performance in goats is that the formal test evaluations that were undertaken in respect of small ruminant testing were conducted using only sheep scrapie samples. It has been shown subsequently that not all tests perform equally in all genotypes of goats (Papasavva‐Stylianou et al., 2017 ; Konold et al., 2020 ; Simmons et al., 2020 ). Not all caprine PRNP polymorphisms are synonymous with ovine ones, and some caprine polymorphisms coincide with particular diagnostic antibody‐binding sites, reducing the sensitivity of individual tests in certain animals.…”
Section: Data and Methodologiesmentioning
confidence: 99%
“…John Spiropoulos, senior veterinary pathologist of the Animal and Plant Health Agency (APHA) (UK), invited speaker, presented the results of two recently published scientific articles of interest, of which he is co-author: 'Transmissible spongiform encephalopathy in goats: is PrP rapid test sensitivity affected by genotype?' (Simmons et al, 2020), and 'The Scrapie Prevalence in a Goat Herd Is Underestimated by Using a Rapid Diagnostic Test' (Konold et al, 2020). The sensitivity of the Rapid test for the detection of TSE in goats (scrapie and BSE) is not 100%, and is influenced by the polymorphisms in certain codons which may alter epitope binding, the rapid test chosen, sampling issues and other still unknown factors.…”
Section: Detection Scrapie In Goats: Rapid Test and Genotypesmentioning
confidence: 99%